Improving Belonging and Connectedness in the Cybersecurity Workforce: From College to the Profession - Mary Beth Klinger (Journal of Cybersecurity Education, Research & Practice, 2024)
This article explores the results of a project aimed at supporting community college students in their academic pursuit of an Associate of Applied Science (AAS) degree in Cybersecurity through mentorship, collaboration, skill preparation, and other activities and touch points to increase students’ sense of belonging and connectedness in the cybersecurity profession. The goal of the project was focused on developing diverse, educated, and skilled cybersecurity personnel for employment within local industry and government to help curtail the current regional cybersecurity workforce gap that is emblematic of the lack of qualified cybersecurity personnel that presently exists nationwide. Emphasis throughout the project was placed on community building so that students felt a part of the cybersecurity community. A project community survey was distributed to students as both a pre-test when they began the project in Year 1 at the start of their cybersecurity coursework, and again as a post-test at the conclusion of Year 2 when they finished their cybersecurity program. Two project cohorts were employed, and the survey questionnaire measured students’ sense of connectedness and level of learning within the project environment. The results showed a marked increase in both constructs from the pre- to post-survey indicating that students felt a greater sense of community as they moved through the project and experienced increased learning through their cybersecurity program. The study concluded that increased feelings of connectedness to the project activities through authentic shared learning experiences promoted belonging and provided social and academic supports to help project students be successful in their cybersecurity academic program and going forward in the in-demand cybersecurity vocation throughout their professional careers.